Model-based definition and enterprise: state-of-the-art and future trend - Goher, Kamran; Shehab, Essam; Al-Ashaab, Ahmed (Sage, 2020)
Model-Based Definition (MBD) is being adopted by the manufacturing industry as a single source for all product information in place of conventional 2D drawings. This paper aims to review the current literature on Model-Based Definition (MBD) and Model-Based Enterprise (MBE) to recognize the main contributions towards the development and implementation of MBD and explore its various perspectives. The publications encompassing technology and applications of MBD are categorized into seven domains. These domains are lifecycle information; design, discrete part manufacturing, and inspection; assembly; maintenance, repair, and overhaul; process planning; engineering change management; and contemporary aspects of digital product definition. The major outcomes of research literature, in these domains, are reviewed and future research directions are identified and formulated. Additionally, the paper highlights the issues and challenges associated with the realization of MBE by the manufacturing industry. These issues are categorized into technical, management, and certification categories. The prevalent issues in each of these categories are further discussed and analyzed
Keywords: Digital Thread; Digital Manufacturing; Manufacturing Industry; State-of-the-art; Model-Based Enterprise; Model-Based Definition